(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Intelligenza artificiale, singolarità tecnologica e diritti umani: uno sguardo nel futuro - 2. Quale religione? Alla ricerca di una definizione costituzionalmente orientata - 3. Transumanesimo, tecnoscienza e religione: una relazione pericolosa? - 4. Non avrai altro Dio al di fuori di AI: Way of the Future e il culto del Dio-computer - 5. (segue) Il transumanesimo a scuola - 6. (segue) Religion or not? La libertà religiosa dei fedeli di Way of the Future - 7. Anche gli androidi sognano divinità elettriche? La libertà religiosa dei robots - 8. Conclusioni: giorni di un futuro passato. Deus ex Machina. Artificial Intelligence and Religious Freedom in the US Constitutional framework ABSTRACT: The raise of the digital age and the developments of Artificial Intelligence is stressing the historical and complicate relationship between science, religion and law. Concepts like technological singularity or transhumanism are rapidly changing this relationship, and a growing number of scientists are now openly describing technological progress in religious terms or even establishing new religions and churches dedicated to the worship of Artificial Intelligence. This cultural and technological revolution is raising up new legal questions: are the traditional legal definition of “Religion” and “Churches” still addressing the challenge raised by new religions based on the worship of AI? Will the Transhumanism change the legal definition of person and his religious rights? Will robots have religious rights under the law? The aim of the paper is to investigate those questions within the of the US Constitutional framework.